(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2024)
Self-medication is a very common practice among the population, as mentioned by Mora (2014) this problem has become a daily occurrence regardless of social class or global character, which has increased rapidly in recent decades, especially in mild diseases such as influenza. The flu is an acute viral infection within the respiratory tract that causes symptoms such as fever and some muscle aches, this disease is not considered a risky one, so pharmaceutical companies consider its remedy as “over-the-counter medicine”, although, over-the-counter medicines must be obtained in a pharmacy or established medical place, as well as those that need some medical prescription, there is a differential in the ease of being able to acquire one before the other, that is why over time over-the-counter drugs became one of the best-selling products worldwide, so its impact on the market is very large and the importance of advertising in this area should be taken into account (Campos, 2014). It is known that there are multiple factors outside advertising such as socioeconomic level, cultural issues, time, etc. that can lead to self-medication (Leonel et al., 2020), in spite of that, this research will focus on observing the relationship between the advertising elements within the audiovisual spots of anti-influenza drugs that induce the citizen of Juarez to self-medicate in order to subsequently collect data and determine if advertising is really a primary factor that affects self-medication in the citizen of Juarez or if it is another of those previously seen.